Comparative study of SmartAmp assay and reverse transcription-polymerase chain reaction by saliva specimen for the diagnosing COVID-19. Issue 1 (January 2022) - Asai, Nobuhiro; Nakamura, Akiko; Sakanashi, Daisuke; Koita, Isao; Ohashi, Wataru; Kawamoto, Yuzuka; Miyazaki, Narimi; Ohno, Tomoko; Yamada, Atsuko; Chida, Sumie; Shibata, Yuichi; Shiota, Arufumi; et al.
Abstract: Introduction: The pandemic of a novel coronavirus disease 2019 (COVID-19) caused by a severe acute respiratory coronavirus 2 (SARS-CoV-2) infection has been problematic worldwide. A new SARS-CoV-2 diagnostic test (SmartAmp) was licensed in Japan in July 2021. This method, which enables us to diagnose COVID-19 as well as a gene mutation on the virus, is promising to reduce medical costs and staff labor. Patients and methods: To analyze the diagnostic accuracy of the SmartAmp assay for diagnosing COVID-19, we performed this retrospective study at our institute during April and May 2021. We compared the results of the SmartAmp assay and real-time reverse transcription-polymerase chain reaction (rRT-PCR) using a saliva sample from individuals suspected as having COVID-19. Results: Out of 70 samples tested, the SmartAmp assay had 50 (71%) positive and 20 (29%) negative results. Using rRT-PCR as a reference, the diagnostic accuracy displayed a sensitivity of 84%, a specificity of 95%, a positive predictive value of 97.7%, and a negative predictive value of 70.4%. On the other hand, false-negative cases were found in 7 (10%), and there was no significant difference of Ct-value between true positive and false negative cases (Mean Ct-value 25.2 vs. 27.5 cycles, p  = 0.226 by Mann-Whitney U test). Conclusion: The SmartAmp assay is a valuable method to diagnose COVID-19 rapidly. However, the negative predictive value is not high enough to diagnose the disease, so that negative results should be considered for rRT-PCR testing if patients are suspected of having COVID-19.